Image quality evaluation method base on digital wavelet transform and vision weighted - JIANG Ming1; MA Zhao-feng1; XIN Yu3; NIU Xin-xin1; YANG Yi-xian1 (Tongxin xuebao)
A new objective method WVWPSNR（wavelet and vision weighted peak signal noise ratio） was presented.In which the method was based on DWT,and the sensitivity of HVS（human visual system） was weighted using sub-band division.In this method,the assessment valued of the new method accord with MOS（mean opinion score）.In order to demonstrate the effectiveness and to verify the reliability of WVWPSNR method,a series of experiment for JPEG、JPEG2000、White Noise、Gaussian Blur and FastFading images were made and tested.The results suggest that the proposed method can provide accurate measures of image quality under JPEG compression.